CHARACTERISTICS OF THIRD-GRADE ELEMENTARY SCHOOL STUDENTS AND THE IMPORTANCE OF STUDENT CHARACTER IDENTIFICATION - Utaminingsih, Esty Setyo; Purwati, Panca Dewi (Research and Development Journal of Education, 2024)
Learning models that do not follow students' needs are one factor that causes low-quality education. Therefore, a teacher in the learning planning process must understand students' characteristics and initial abilities to adjust to their needs. The method used in this study is qualitative, using a descriptive approach. The sampling technique used is total sampling (all students), which is 15 students. The data collection techniques were observation, interviews, and documentation for four weeks in third grade at Gombang State Elementary School. The characteristics of third-grade students of Gombang State Elementary School include learning from concrete things, 2) hierarchical, 3) liking to group in doing activities, 4) doing/demonstrating something directly, 5) having mastered more than 3,500 words and in the semantic phase, 6) highly curious about something. The importance of identifying the characteristics of students is to optimize student needs so that learning programs in elementary schools will be effective because they are based on the characteristics and needs of students.